Food systems Diversification through Nutri-Cereals and Pulses – Lessons Learnt from Asia and Africa - Afari-Sefa, Victor; Deevi, Kumara Charyulu; Bose, Disha; Guvvalavenkata, Anupama (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The policy brief highlights diversification experiences in Asia and Africa, diversification towards nutri-cereals and pulses in the last two decades, and the relationship between the income levels of major countries and their food systems diversification across regions. Further, the brief also synthesizes the major drivers and challenges for agricultural transformation across regions. Finally, it concludes with key lessons learnt under food systems diversification in Asia and Africa regions.